CLIMATE CHANGE AND FISCAL SUSTAINABILITY: RISKS AND OPPORTUNITIES. (2021) - Agarwala, Matthew; Burke, Matt; Klusak, Patrycja; Mohaddes, Kamiar; Volz, Ulrich; Zenghelis, Dimitri
Abstract : Both the physical and transition-related impacts of climate change pose substantial macroeconomic risks. Yet, markets still lack credible estimates of how climate change will affect debt sustainability, sovereign creditworthiness and the public finances of major economies. We present a taxonomy for tracing the physical and transition impacts of climate change through to impacts on sovereign risk. We then apply the taxonomy to the UK's potential transition to net zero. Meeting internationally agreed climate targets will require an unprecedented structural transformation of the global economy over the next two or three decades. The changing landscape of risks warrants new risk management and hedging strategies to contain climate risk and minimise the impact of asset stranding and asset devaluation. Yet, conditional on action being taken early, the opportunities from managing a net zero transition would substantially outweigh the costs.